2003
DOI: 10.1046/j.1365-2613.2003.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell adhesion molecules in leukocyte recruitment in the liver and gut

Abstract: Summary. This article reviews the evidence that adhesion molecules are critical in leukocyte recirculation and pathogenesis of diseases affecting the closely related tissues of the liver and gut, which offer novel opportunities for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 84 publications
1
52
0
Order By: Relevance
“…Several lines of evidence have been proposed for the exact mechanisms involved in the development of IRI; however, the exact underlying mechanisms remain unclear [24]. Disturbance of the hepatic microcirculation [43] combined with cellular interaction between platelets [44], leukocytes [45], and endothelial lining cells [46], various Kupffer cell-derived proinflammatory mediators such as TNF-a, interleukin-1, and free radicals [47,48], and the expression of adhesion molecules are important determinants of the pathophysiologic changes that happen during IRI [24,49,50]. In the present study Kupffer cells showed enhanced capacity for phagocytosis of latex beads after CO 2 pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have been proposed for the exact mechanisms involved in the development of IRI; however, the exact underlying mechanisms remain unclear [24]. Disturbance of the hepatic microcirculation [43] combined with cellular interaction between platelets [44], leukocytes [45], and endothelial lining cells [46], various Kupffer cell-derived proinflammatory mediators such as TNF-a, interleukin-1, and free radicals [47,48], and the expression of adhesion molecules are important determinants of the pathophysiologic changes that happen during IRI [24,49,50]. In the present study Kupffer cells showed enhanced capacity for phagocytosis of latex beads after CO 2 pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…14-16 Membranous ICAM-1 and VCAM-1 and transmembrane protein Eselectin mediate adhesion and interactions between cells or a cell and extracellular matrix 17 ; thus, their expression levels were determined. Ox-LDL treatment induced intensive membrane fluorescence, suggesting the increased membrane expression of ICAM-1, VCAM-1, and E-selectin, which was significantly inhibited by CPT, NAC, or BAY117082 pretreatment (Fig.…”
Section: Cpt Inhibited Ox-ldl-induced Membrane Adhesion Molecule Exprmentioning
confidence: 99%
“…Endothelial cell activation and surface upregulation of selectins are necessary parts in the localization of leukocytes at sites of tissue injury (2). Indeed, numerous studies have shown that P-, E-, and L-selectin support early interactions between leukocytes and endothelial cells at sites of inflammation (13,19,21,28).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, neutrophil stiffness increases, promoting mechanical sequestration of neutrophils in lung capillaries (20,34). It is widely held that leukocyte rolling is mediated by the selectin family of adhesion molecules, including P-, E-and L-selectins although their relative roles appear to be both tissue-and stimulus-dependent (2,28). Selectin ligands are complex glycoproteins and, in terms of selectin specificity and function, are poorly understood.…”
mentioning
confidence: 99%